2019
DOI: 10.1097/fjc.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation Versus Antiarrhythmic Drug Therapy for Atrial Fibrillation: Meta-analysis of Safety and Efficacy

Abstract: Background: Radiofrequency ablation (RFA) and antiarrhythmic drugs (AADs) are the main treatments used for atrial fibrillation (AF). In recent years, a number of articles comparing the 2 treatments have begun to emerge. Though, the influence of follow-up time in the meta-analysis was not considered in these articles. However, more recently, large-scale clinical trial articles have included follow-up with the patients up to 5 years after treatment. Therefore, the aim of this study was to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Although there are several documented complications of RFA like pulmonary venous thrombosis, pulmonary venous stenosis, left atrial hematoma, etc., AEF is considered to be one of the most dreadful and fatal complications of RFA [ 6 ]. The first documented case of AEF as a complication of RFA was described in the year 2004 by Pappone et al [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several documented complications of RFA like pulmonary venous thrombosis, pulmonary venous stenosis, left atrial hematoma, etc., AEF is considered to be one of the most dreadful and fatal complications of RFA [ 6 ]. The first documented case of AEF as a complication of RFA was described in the year 2004 by Pappone et al [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Classic antiarrhythmic drug treatment not only has poor curative effects and a high recurrence rate, but will also inevitably produce toxic side effects after long-term use ( 38 , 39 ). Although there are various ablation strategies in the clinical practice of AF treatment, in general, neither endocardial catheter ablation nor surgical ablation has achieved satisfactory results in the success rate of AF elimination ( 3 , 40 45 ), and there is a significant learning curve; experienced medical centers are far more effective than those with fewer deployments ( 46 , 47 ). The CABANA trial showed that 36.4% of catheter ablation patients experienced recurrence of AF within 12 months after surgery, and 18.4% of catheter ablation patients developed symptomatic AF throughout follow-up ( 48 ).…”
Section: The Main Traditional Treatment Strategies For Afmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is one of the leading approaches to rhythm control in atrial re-entry arrhythmias. It is a first-choice treatment tactic in symptomatic and high-risk atrial flutter and often prescribed to atrial fibrillation (AF) patients with drug inefficiency or intolerance [1,2]. RFA -isolation of pulmonary veins for AF and RFA of cava-tricuspid isthmus in right atria for flutter treatment could be used alone or simultaneously to increase the efficiency of a single procedure [3,4].…”
Section: Introductionmentioning
confidence: 99%